Zur Lage der bürgerlichen Demokratie in Deutschland - Lessenich, Stephan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
Contemporary welfare states are confronted with what may be called a new "social question": How should and can welfare losses be distributed among the population of an affiuent society? The article claims that social policy-makers in Germany try to solve this problem by inciting and reproducing the middle classes’ envy of all those who are said to undeservedly profit from collective solidarity. In a sense, the widespread fear of "too much" democracy and individualism, identified by Max Weber almost a century ago, is being revived under new circumstances. (And nobody - Max Weber not being with us anymore - seems to care.)